Looking beyond place branding: the emergence of place reputation. Issue 3 (10th October 2016) - Bell, Fraser
Abstract : Purpose: As place branding is reaching an impasse in terms of its development with numerous shortcomings being uncovered, this commentary suggests that the practice can be repositioned as part of the more comprehensive notion of place reputation. By building on the idea of corporate reputation and embryonic evidence of its application to geographical entities, this paper aims to argue for a more substantial translation of this concept to cities and regions. Design/methodology/approach: This idea was investigated through empirical work in English second-tier cities, specifically concerning semi-structured interviews with local and regional stakeholders on the topic of place reputation conducted in 2014. Findings: The empirical work found that place branding and place reputation can remain complimentary to one another, are entwined and are problematic to disentangle. This discovered that place branding is not as effective when used in isolation, and the concept benefits from the support of a more comprehensive reputation management strategy. In addition, this study found that the idea of reputational capital is a key theory for the development of reputation, allowing this broad notion to be tackled in terms of audiences, domains and sectors. Originality/value: Moreover, this commentary constitutes a novel piece of research, and this is achieved by exploring gaps in both interdisciplinary place branding and corporate literatures of reputation being applied to place. This is addressed from a relational economic geography perspective, with the support of reputational capital which has links to Pierre Bourdieu's (1986) Forms of Capital, this seeks to raise issues and add value to current place branding debates.